Bryophytes as indicators of recovery posttechnogenic landscapes of sulfur extraction (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
45 bryophytes species on not recultivated areas of sulfur mining dump, and 32 species on recultivated areas were found. Biomorphological analysis of mosses was provided. Wefts and turfs are dominates mosses biomorfs on not recultivated areas. Turf is widespread biomorfs on recultivated areas. Most species of mosses from not recultivated areas are mesotrophic mesophytes and xeromesophytes which grows on wide substrate specter. However, terricolous mesotrophic xeromesophytes and mesoeutrophical gigromesophytes mosses are present in recultivated areas. According to our research, recultivation can significantly stabilize the micro-climatic and edaphic conditions. The results are suggest an important role of bryophytes as indication of vegetation condition on devastated areas and monitoring of their restoration.
Keywords: mosses, life forms, life strategies, projective cоvering, biomass, dumps of sulfur extraction.